ANALISA PEMROSESAN PARALEL UNTUK KOMPRESI DAN DEKOMPRESI DATA - Wilhelmus Wajo Kelen; Dwi Nugraheny (Compiler, 2015)
Parallel processing system is a collection of computers connected and work together as an integrated computer resources to complete certain jobs which are connected by the network, so it can be seen as one - unity. Parallel processing can be applied to such work compress and decompression the data. Compression process is a way to compress the data so that it requires less storage space, while the decompression process is the process of restoring data to its original shape. The utilization of parallel processing to speed up or get more speed on the efficiency of the data compression so the job. The work came to be divided to parallel computers that are not doing the work.